2000
DOI: 10.1046/j.1460-9592.2000.00532.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ropivacaine 0.1% and 0.2% with bupivacaine 0.2% for single‐shot caudal anaesthesia in children

Abstract: We compared analgesic efficacy and degree of motor block induced by ropivacaine 0.1% (R 0.1) and 0.2% (R 0.2) vs. bupivacaine 0.2% (B 0. 2) after caudal anaesthesia in children. Total and free plasma concentrations were measured after caudal injection. Duration of caudal analgesia (median/range) was significantly shorter in group R 0.1 (1.7 h/0.2-6 h) than in group R 0.2 (4.5 h/1.7-6 h) or group B 0. 2 (4 h/1-6 h) (P<0.05). Motor block in the first 2 h postoperatively was significantly less for both ropivacain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 24 publications
1
49
0
3
Order By: Relevance
“…Further studies are required to determine whether adding epinephrine to ropivacaine results in a prolonged duration of action and whether it effectively helps in detecting an iv injection. 22 C max = maximal plasma concentration; T max = time to C max ; Cl = clearance; Vd = distribution volume; plain = plain ropivacaine; E + = ropivacaine + epinephrine; NA = results not available.…”
Section: Part 2: Population Analysis Using Nonmemmentioning
confidence: 99%
“…Further studies are required to determine whether adding epinephrine to ropivacaine results in a prolonged duration of action and whether it effectively helps in detecting an iv injection. 22 C max = maximal plasma concentration; T max = time to C max ; Cl = clearance; Vd = distribution volume; plain = plain ropivacaine; E + = ropivacaine + epinephrine; NA = results not available.…”
Section: Part 2: Population Analysis Using Nonmemmentioning
confidence: 99%
“…Seventeen such RCTs were reviewed in detail using a structured methodology. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Two review articles were also identified. 18,19 The reference lists for all of these 19 publications were reviewed to identify any further RCTs that may have been missed with the initial search strategy; no such study was found.…”
Section: Methodsmentioning
confidence: 99%
“…Overall, it appears that most of the studies (with two notable exceptions) included in this evidence-based clinical update compared ''nearly'' equipotent doses of the drugs. 5,17 This then represents a slight weakness in the methodology of most of the studies reviewed.…”
Section: Comment On Relative Potencymentioning
confidence: 99%
“…Some authors have reported that, during pediatric tonsillectomies, peritonsillar infiltration of bupivacaine and ropivacaine are equally effective 36 , whereas others have reported that bupivacaine provides superior pain relief 37 . When used caudally in children, ropivacaine and bupivacaine have been reported to be equally effective [38][39][40] . Comparisons of the two drugs as intra-articular injections either have shown no difference in effectiveness 41 or have shown ropivacaine to be more effective than bupivacaine 14 .…”
mentioning
confidence: 99%
“…In a meta-analysis of the analgesic efficacy of intra-articular injections, there was a nonsignificant difference (p = 0.196) in the dose of local anesthetics given in the studies that demonstrated a significant positive effect of intra-articular injection on postoperative pain as compared with studies that demonstrated no effect. Furthermore, Luz et al reported that single shot of caudal anesthesia with 0.1% ropivacaine was significantly less effective than 0.2% bupivacaine in children, but when a equipotent concentration (0.2%) was used, ropivacaine was found to be equally as effective 40 . Because of differences in the concentrations of the local in the present study anesthetics (0.20% compared with 0.25%), the mean difference in the dose of the local anesthetic administered in the ropivacaine and bupivacaine groups was 0.04 mg/kg.…”
mentioning
confidence: 99%